European College of Equine Internal Medicine consensus statement on equine flaviviridae infections in Europe - Jessika‐M. V. Cavalleri; Orsolya Korbacska‐Kutasi; Agnès Leblond; Romain Paillot; Nicola Pusterla; Eike Steinmann; Joy Tomlinson (Journal of Veterinary Internal Medicine, 2022)
Abstract Horses and other equids can be infected with several viruses of the family Flaviviridae, belonging to the genus Flavivirus and Hepacivirus. This consensus statement focuses on viruses with known occurrence in Europe, with the objective to summarize the current literature and formulate clinically relevant evidence‐based recommendations regarding clinical disease, diagnosis, treatment, and prevention. The viruses circulating in Europe include West Nile virus, tick‐borne encephalitis virus, Usutu virus, Louping ill virus and the equine hepacivirus. West Nile virus and Usutu virus are mosquito‐borne, while tick‐borne encephalitis virus and Louping ill virus are tick‐borne. The natural route of transmission for equine hepacivirus remains speculative. West Nile virus and tick‐borne encephalitis virus can induce encephalitis in infected horses. In the British Isle, rare equine cases of encephalitis associated with Louping ill virus are reported. In contrast, equine hepacivirus infections are associated with mild acute hepatitis and possibly chronic hepatitis. Diagnosis of flavivirus infections is made primarily by serology, although cross‐reactivity occurs. Virus neutralization testing is considered the gold standard to differentiate between flavivirus infections in horses. Hepacivirus infection is detected by serum or liver RT‐PCR. No direct antiviral treatment against flavi‐ or hepacivirus infections in horses is currently available and thus, treatment is supportive. Three vaccines against West Nile virus are licensed in the European Union. Geographic expansion of flaviviruses pathogenic for equids should always be considered a realistic threat, and it would be beneficial if their detection was included in surveillance programs.